SENTACUP: Ulilization of cellulose from tea dregs waste as a waterproof biodegradable cup to support circular economy and environmental sustainability - Terrencia, Giselle; Dewantara, Abednego Reiki; Prabawa, Haykal Zahran (EcoVision: Journal of Environmental Solutions, 2026)
Background: The extensive use of single-use plastic cups has caused serious environmental problems, including plastic accumulation and microplastic pollution. At the same time, tea-processing industries generate large quantities of spent tea waste that remain underutilized despite their high cellulose content. This study aims to propose an innovative and sustainable solution by utilizing cellulose extracted from spent tea waste to produce a biodegradable and water-resistant cup that supports circular economy principles. Methods: This study employed an experimental and material development approach. Spent tea waste was collected, sorted, dried, and milled to obtain uniform particles. The cellulose-rich material was blended with cassava starch as a natural binder and molded using a press-molding technique. A natural wax coating was applied to improve water resistance. The developed product was evaluated through mechanical strength tests, water absorption tests, water resistance tests, and biodegradability assessment, supported by descriptive and comparative analysis. Findings: The results indicate that SentaCup has sufficient mechanical strength for beverage containers, demonstrates good resistance to water, and is capable of biodegrading within approximately 90–120 days. The utilization of cellulose as a natural polymer contributes to structural strength, flexibility, and thermal stability. This innovation shows strong potential as an environmentally friendly alternative to conventional single-use plastic cups while adding value to organic waste. Conclusion: The development of SentaCup demonstrates that spent tea waste can be effectively transformed into a functional, biodegradable, and water-resistant cup. This innovation contributes to reducing plastic waste, supporting circular resource management, and promoting environmental sustainability. Novelty/Originality of this article: The novelty aspect refers to the new or innovative elements in a research study that distinguish it from previous work. It includes unique contributions, new methods, or findings that have not been explored before in the field.